Bipolar spectrum disorders in neurologic disorders - Digiovanni, Anna; Ajdinaj, Paola; Russo, Mirella; Sensi, Stefano L.; Onofrj, Marco; Thomas, Astrid (Frontiers in Psychiatry, 2022)
Psychiatric symptoms frequently predate or complicate neurological disorders, such as neurodegenerative diseases. Symptoms of Bipolar Spectrum Disorders (BSD), like mood, behavioral, and psychotic alterations, are known to occur – individually or as a syndromic cluster – in Parkinson’s Disease and in the behavioral variant of FrontoTemporal Dementia. Nonetheless, due to shared pathophysiological mechanisms, or genetic predisposition, several other neurological disorders show significant, yet neglected, clinical and biological overlaps with BSD like neuroinflammation, ion channel dysfunctions, neurotransmission imbalance, or neurodegeneration. BSD pathophysiology is still largely unclear, but large-scale network dysfunctions are known to participate in the onset of mood disorders and psychotic symptoms. Thus, functional alterations can unleash BSD symptoms years before the evidence of an organic disease of the central nervous system. The aim of our narrative review was to illustrate the numerous intersections between BSD and neurological disorders from a clinical-biological point of view and the underlying predisposing factors, to guide future diagnostic and therapeutical research in the field.